The macroeconomic effects of inflation uncertainty - Norbert Metiu; Esteban Prieto (Deutsche Bundesbank, 2023)
The uncertainty of U.S. core inflation, measured by the stochastic volatility of forecast errors, has soared to a level not seen in nearly five decades since the COVID-19 pandemic hit the global economy. Prices, consumption, and production increase after a positive shock to core inflation uncertainty in a vector autoregression. Endogenous changes in household inflation expectations help to understand the transmission mechanism through which an inflation uncertainty shock generates positive demand effects. Households expect significantly higher inflation when confronted with a surprise increase in the uncertainty of core consumer prices. In turn, they consume more, which boosts aggregate demand.
Keywords: E31; E32; 330; Household Expectations; Inflation; Uncertainty; Stochastic Volatility; Structural VAR